Manajemen Fisioterapi dalam Meningkatkan Kebugaran pada Pasien Pasca Covid-19 : Studi Kasus - Nova Relida Samosir (Jurnal Ilmu Kesehatan Abdurrab, 2023)
Background: Post covid or long covid is a general term used for people who have recovered from Covid-19 but still show symptoms much longer than expected. Research purposes; to determine the effectiveness of the Diaphragm Breathing Exercise intervention in increasing fitness in post-Covid-19 patients. Research method: case study method, presented in the form of a description. The study was conducted at the Abdurrab University Physiotherapy Laboratory for 3 weeks. Conclusion; Post-covid-19 patients with less than optimal fitness conditions received the Diaphragm Breathing Exercise intervention 9 times, the results obtained, there was an increase in fitness with a Vo2 Max value of 30.08 (Very Bad) after the intervention, there was a change in increase in Vo2 Max with a value of 42.68 (Good).